2005
DOI: 10.1007/s10995-005-4871-9
|View full text |Cite
|
Sign up to set email alerts
|

Health Promotion and Psychosocial Services and Women’s Assessments of Interpersonal Prenatal Care in Medicaid Managed Care

Abstract: Prenatal health promotion and psychosocial services have associated benefits to enrollees that should matter to Medicaid health plans and their providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 29 publications
1
33
0
1
Order By: Relevance
“…Variations in health promotion content might be related to variations in patient-provider communication. Another study with ethnic low-income women receiving prenatal care found that receiving prenatal health promotion advice was associated with higher quality interpersonal care (communication, decision making and interpersonal style) and satisfaction, an important outcome and indicator of the quality of care (Korenbrot et al, 2005). Therefore, in our study, higher quality patient-provider communication might have contributed to discussion of more topics.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Variations in health promotion content might be related to variations in patient-provider communication. Another study with ethnic low-income women receiving prenatal care found that receiving prenatal health promotion advice was associated with higher quality interpersonal care (communication, decision making and interpersonal style) and satisfaction, an important outcome and indicator of the quality of care (Korenbrot et al, 2005). Therefore, in our study, higher quality patient-provider communication might have contributed to discussion of more topics.…”
Section: Discussionmentioning
confidence: 59%
“…Wide variations have also been found in the proportion of women who report receiving recommended advice on health promotion topics with a range from 21% to 98% (Korenbrot, Wong, & Stewart, 2005;Petersen, Connelly, Martin, & Kupper, 2001;Sable & Herman, 1997;Vonderheid, Montgomery, & Norr, 2003;Yu & Jackson, 1995). Data from the Pregnancy Risk Assessment Monitoring System (PRAMS) for 1997 and 1998 (Petersen et al, 2001) also indicated that women at higher need based on five topics (cigarette use, alcohol use, breastfeeding, partner violence, and preterm labor) did not receive adequate coverage of health promotion content.…”
Section: Prenatal Health Promotion Contentmentioning
confidence: 99%
“…Positive experiences with prenatal care are strong predictors of consistent use of paediatric and preventive health services. [39][40][41] This exploratory study showed a discrepancy between patients' and providers' perceptions of the offering of anticipatory guidance during the prenatal healthcare experience. These results show physical abuse, folic acid and seat-belt use were not talked about regularly by providers nor remembered by patients in the four Friendly Access pilot communities.…”
Section: Resultsmentioning
confidence: 80%
“…Most have lacked a theoretical framework (Handler et al, 1998. ; Korenbrot et al, 2005). One quantitative study described the content and process of communication during prenatal care; but, it was with women of advanced maternal age (>33 year old) and over 75% of the population was white (Roter, Geller, Bernhardt, Larson, & Doksum, 1999).…”
Section: Patient-provider Communication During Prenatal Carementioning
confidence: 99%
“…In addition, dimensions of prenatal interpersonal processes of care that were associated with greater satisfaction among pregnant African American women were communication and provider interpersonal style (Korenbrot et al, 2005). …”
Section: Patient-provider Communication During Prenatal Carementioning
confidence: 99%